2018
DOI: 10.1021/acsomega.8b03182
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted Reinforcement of Macrophage Reprogramming Toward M2 Polarization by IL-4-Loaded Hyaluronic Acid Particles

Abstract: Alteration of macrophage polarization from inflammatory (M1) to anti-inflammatory (M2) phenotype can have striking implications for the regeneration of injured tissues, treatment of inflammatory diseases, and relief of autoimmune disorders. Although certain cytokines like interleukin (IL)-4 and IL-13 are capable of inducing M2 macrophage polarization, their therapeutic potential in vivo is suffering from low efficacy due to their instability and poor access to target cells. Here, we report the synthesis of IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…IL-4 is a potent inducer for M2 macrophage polarization and differentiation (Supplementary Fig. 1), consistent with previous studies [27]. We found that a co-culture of IL-4-induced M2 macrophages and HTECs signi cantly attenuated hypoxia-induced upregulation of proin ammatory cytokines IL-6, IL-8, and TNF-α (Fig.…”
Section: M2 Macrophages Prevent Hypoxia-induced Proin Ammatory Reactisupporting
confidence: 91%
“…IL-4 is a potent inducer for M2 macrophage polarization and differentiation (Supplementary Fig. 1), consistent with previous studies [27]. We found that a co-culture of IL-4-induced M2 macrophages and HTECs signi cantly attenuated hypoxia-induced upregulation of proin ammatory cytokines IL-6, IL-8, and TNF-α (Fig.…”
Section: M2 Macrophages Prevent Hypoxia-induced Proin Ammatory Reactisupporting
confidence: 91%
“…Beyond this, it is conceivable that the decrease of the pro-inflammatory tissue response is an indicator for a preponderance of anti-inflammatory reactivity. This would mean that the addition of higher concentrations of HMWHY leads the tissue response towards an M2-driven reaction, which has assumed to be correlated with tissue healing [62]. Thus, a higher level of bone regeneration might have been induced after the time point analyzed in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…While the backpacks described here bind to macrophage surfaces, other designs can be conceived to attach to other circulatory cells with higher chemotactic sensitivity (17,18,55). Also, a range of immunomodulatory payloads can be considered, including those that facilitate adaptive immune responses toward a backpack-based vaccine (52) or promote anti-inflammatory phenotypes to aid in tissue regeneration or repair for autoimmune diseases (56,57). PDMS template preparation PDMS templates were prepared by soft lithography using methods similar to those described previously (16).…”
Section: Discussionmentioning
confidence: 99%